Pathogenesis and virulence of Candida albicans and Candida glabrata - Henriques, Mariana (2020)
Fungal infections in humans have historically received comparatively less attention than those caused by bacteria and viruses. This may, in part, stem from the relative differences in infection prevalence. However, the more widespread use of immunosuppressive therapy, invasive surgery and medical devices in modern medicine has resulted in a more frequent occurrence of human fungal infection. There are a number of fungi that can cause human disease. However, it is arguably a species of the genus Candida that are most often encountered. There are over 150 Candida species that are widely encountered in the environment and in animal hosts, however, only a small number are opportunistic pathogens of humans. Candida albicans is a polymorphic yeast-like fungus and undoubtedly the species most often recovered from human infection. As such, the virulence of C. albicans and its susceptibility to antifungal agents are often investigated. More recently, the prevalence of infections caused by non-C. albicansCandida species have increased and, amongst these, infections caused by Candida glabrata have received attention given its often-higher tolerance to frequently used antifungals exhibited by this species. The papers presented in this Special Issue have focused on aspects relating to host responses to Candida infection, the efficacy of novel therapeutic agents and also treatment regimes. The papers highlight novel findings in their respective areas, whilst also highlighting the need for further research in these key and largely under-researched areas of candidoses.